Targeting ASIC3 for Relieving Mice Fibromyalgia Pain: Roles of Electroacupuncture, Opioid, and Adenosine - Yen, Liang-Ta (Sci Rep, 2017)
Many scientists are seeking better therapies for treating fibromyalgia (FM) pain. We used a mouse model of FM to determine if ASIC3 and its relevant signaling pathway participated in FM pain. We demonstrated that FM-induced mechanical hyperalgesia was attenuated by electroacupuncture (EA). The decrease in fatigue-induced lower motor function in FM mice was also reversed by EA. These EA-based effects were abolished by the opioid receptor antagonist naloxone and the adenosine A1 receptor antagonist rolofylline. Administration of opioid receptor agonist endomorphin (EM) or adenosine A1 receptor agonist N(6)-cyclopentyladenosine (CPA) has similar results to EA. Similar results were also observed in ASIC3(−/−) or ASIC3 antagonist (APETx2) injected mice. Using western blotting, we determined that pPKA, pPI3K, and pERK were increased during a dual acidic injection priming period. Nociceptive receptors, such as ASIC3, Nav1.7, and Nav1.8, were upregulated in the dorsal root ganglion (DRG) and spinal cord (SC) of FM mice. Furthermore, pPKA, pPI3K, and pERK were increased in the central thalamus. These aforementioned mechanisms were completely abolished in ASIC3 knockout mice. Electrophysiological results also indicated that acid potentiated Nav currents through ASIC3 and ERK pathway. Our results highlight the crucial role of ASIC3-mediated mechanisms in the treatment of FM-induced mechanical hyperalgesia.